Direct targeting of FOXP3 in Tregs with AZD8701, a novel antisense oligonucleotide to relieve immunosuppression in cancer. Issue 4 (6th April 2022) - Revenko, Alexey; Carnevalli, Larissa S; Sinclair, Charles; Johnson, Ben; Peter, Alison; Taylor, Molly; Hettrick, Lisa; Chapman, Melissa; Klein, Stephanie; Solanki, Anisha; Gattis, Danielle; Watt, Andrew; et al.
Abstract : Background: The Regulatory T cell (Treg) lineage is defined by the transcription factor FOXP3, which controls immune-suppressive gene expression profiles. Tregs are often recruited in high frequencies to the tumor microenvironment where they can suppress antitumor immunity. We hypothesized that pharmacological inhibition of FOXP3 by systemically delivered, unformulated constrained ethyl-modified antisense oligonucleotides could modulate the activity of Tregs and augment antitumor immunity providing therapeutic benefit in cancer models and potentially in man. Methods: We have identified murine Foxp3 antisense oligonucleotides (ASOs) and clinical candidate human FOXP3 ASO AZD8701. Pharmacology and biological effects of FOXP3 inhibitors on Treg function and antitumor immunity were tested in cultured Tregs and mouse syngeneic tumor models. Experiments were controlled by vehicle and non-targeting control ASO groups as well as by use of multiple independent FOXP3 ASOs. Statistical significance of biological effects was evaluated by one or two-way analysis of variance with multiple comparisons. Results: AZD8701 demonstrated a dose-dependent knockdown of FOXP3 in primary Tregs, reduction of suppressive function and efficient target downregulation in humanized mice at clinically relevant doses. Surrogate murine FOXP3 ASO, which efficiently downregulated Foxp3 messenger RNA and protein levels in primary Tregs, reduced Treg suppressive function in immune suppression assays in vitro. FOXP3 ASO promoted more than 70% reduction in FOXP3 levels in Tregs in vitro and in vivo, strongly modulated Treg effector molecules (eg, ICOS, CTLA-4, CD25 and 4-1BB), and augmented CD8 + T cell activation and produced antitumor activity in syngeneic tumor models. The combination of FOXP3 ASOs with immune checkpoint blockade further enhanced antitumor efficacy. Conclusions: Antisense inhibitors of FOXP3 offer a promising novel cancer immunotherapy approach. AZD8701 is being developed clinically as a first-in-class FOXP3 inhibitor for the treatment of cancer currently in Ph1a/b clinical trial (NCT04504669 ).